2011
DOI: 10.1007/s11832-010-0309-z
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcome in the most severely affected Legg-Perthes patients, comparing prolonged traction in abduction with femoral varus derotation treatment

Abstract: Purpose Compare conservative and operative treatment in the most severely affected Legg-Perthes disease patients. Methods 29 patients (14 conservative and 15 operative) with 32 affected hips (16 conservative and 16 operative) were evaluated, all Catterall 3 or 4. The conservative group, with a median age-at-onset of 4.8 (range, 2.5-9.5) years, was treated by a rigorous regime of traction in abduction for an average of two years. Follow-up was performed at a median of 28.6 (range, 17.4-31.6) years with a median… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…Similar findings were observed in the studies done by the various researchers from different countries. 2,15 In this study involvement of hip, onset and character of pain of all the subjects in both groups were almost similar and there were no statistically significant differences. But statistically significant difference was observed in duration of pain in between the groups.…”
Section: Discussionsupporting
confidence: 51%
“…Similar findings were observed in the studies done by the various researchers from different countries. 2,15 In this study involvement of hip, onset and character of pain of all the subjects in both groups were almost similar and there were no statistically significant differences. But statistically significant difference was observed in duration of pain in between the groups.…”
Section: Discussionsupporting
confidence: 51%
“…15 Similarly, a few clinical studies have endorsed this view. 3,4,16,17 The impression that weight-bearing in the early stages of LCPD predisposes to deformation of the femoral head has been recently supported by the findings in a novel MRI study. 18 The study demonstrated flattening and widening of the epiphysis as soon as children with LCPD who were early in the course of the disease bore weight on the limb.…”
Section: Weight Relief and Containmentmentioning
confidence: 87%
“…However, experimental studies have shown that weight relief does have a definite protective effect on the shape of the femoral head following ischemic necrosis 15. Similarly, a few clinical studies have endorsed this view 3,4,16,17. The impression that weight-bearing in the early stages of LCPD predisposes to deformation of the femoral head has been recently supported by the findings in a novel MRI study 18.…”
Section: Discussionmentioning
confidence: 97%
“…2 Although the extensive literature pertaining to LCPD, there is still a gap in our knowledge about its risk factors, etiology and preventive strategies. 1,3,4 LCPD is a multifactorial disorder and apparently both genetic and environmental factors have been implicated in its etiopathogenic mechanisms. 2 However, a few familial cases with autosomal dominant inheritance due to mutations in a single gene such as COL2A1 have been reported.…”
Section: Introductionmentioning
confidence: 99%